Increasing the etanercept dose in a treat-to-target approach in juvenile idiopathic arthritis: does it help to reach the target? A post-hoc analysis of the BeSt for Kids randomised clinical trial - Bastiaan T. van Dijk; Sytske Anne Bergstra; J. Merlijn van den Berg; Dieneke Schonenberg-Meinema; Lisette W.A. van Suijlekom-Smit; Marion A.J. van Rossum; Yvonne Koopman-Keemink; Rebecca ten Cate; Cornelia F. Allaart; Daniëlle M.C. Brinkman; Petra C.E. Hissink Muller (BMC, 2024)
Abstract Background Etanercept has been studied in doses up to 0.8 mg/kg/week (max 50 mg/week) in juvenile idiopathic arthritis (JIA) patients. In clinical practice higher doses are used off-label, but evidence regarding the relation with outcomes is lacking. We describe the clinical course of JIA-patients receiving high-dose etanercept (1.6 mg/kg/week; max 50 mg/week) in the BeSt for Kids trial. Methods 92 patients with oligoarticular JIA, RF-negative polyarticular JIA or juvenile psoriatic arthritis were randomised across three treat-to-target arms: (1) sequential DMARD-monotherapy (sulfasalazine or methotrexate (MTX)), (2) combination-therapy MTX + 6 weeks prednisolone and (3) combination therapy MTX + etanercept. In any treatment-arm, patients could eventually escalate to high-dose etanercept alongside MTX 10mg/m2/week. Results 32 patients received high-dose etanercept (69% female, median age 6 years (IQR 4-10), median 10 months (7-16) from baseline). Median follow-up was 24.6 months. Most clinical parameters improved within 3 months after dose-increase: median JADAS10 from 7.2 to 2.8 (p = 0.008), VAS-physician from 12 to 4 (p = 0.022), VAS-patient/parent from 38.5 to 13 (p = 0.003), number of active joints from 2 to 0.5 (p = 0.12) and VAS-pain from 35.5 to 15 (p = 0.030). Functional impairments (CHAQ-score) improved more gradually and ESR remained stable. A comparable pattern was observed in 11 patients (73% girls, median age 8 (IQR 6-9)) who did not receive high-dose etanercept despite eligibility (comparison group). In both groups, 56% reached inactive disease at 6 months. No severe adverse events (SAEs) occurred after etanercept dose-increase. In the comparison group, 2 SAEs consisting of hospital admission occurred. Rates of non-severe AEs per subsequent patient year follow-up were 2.27 in the high-dose and 1.43 in the comparison group. Conclusions Escalation to high-dose etanercept in JIA-patients who were treated to target was generally followed by meaningful clinical improvement. However, similar improvements were observed in a smaller comparison group who did not escalate to high-dose etanercept. No SAEs were seen after escalation to high-dose etanercept. The division into the high-dose and comparison groups was not randomised, which is a potential source of bias. We advocate larger, randomised studies of high versus regular dose etanercept to provide high level evidence on efficacy and safety. Trial registration Dutch Trial Register; NTR1574; 3 December 2008; https://onderzoekmetmensen.nl/en/trial/26585 .